1995
DOI: 10.1073/pnas.92.18.8264
|View full text |Cite
|
Sign up to set email alerts
|

Decreased atherosclerosis in mice deficient in both macrophage colony-stimulating factor (op) and apolipoprotein E.

Abstract: To develop a murine model system to test the role of monocyte-derived macrophages in atherosclerosis, the osteopetrotic (op) mutation in the macrophage colonystimulating factor gene was bred onto the apolipoprotein E (apoE)-deficient background. The doubly mutant (op/apoEdeficient) mice fed a low-fat chow diet had significantly smaller proximal aortic lesions at an earlier stage of progression than their apoE-deficient control littermates. These lesions in the doubly mutant mice were composed of macrophage foa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
378
3
19

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 618 publications
(425 citation statements)
references
References 30 publications
(32 reference statements)
18
378
3
19
Order By: Relevance
“…This finding confirms the hypolipidaemic effect of M-CSF that had been observed in humans, primates, and rabbits [50][51][52]. However, these apoE-deficient op mice had paradoxically fourto 10-fold smaller aortic root lesions than their controls [45]. Thus, this study proves the proatherogenic role of monocyte-derived macrophages, as fewer monocyte-macrophages led to smaller lesions despite higher levels of proatherogenic lipoprotein particles.…”
Section: Apoe Deficiency-induced Atherosclerosissupporting
confidence: 86%
See 3 more Smart Citations
“…This finding confirms the hypolipidaemic effect of M-CSF that had been observed in humans, primates, and rabbits [50][51][52]. However, these apoE-deficient op mice had paradoxically fourto 10-fold smaller aortic root lesions than their controls [45]. Thus, this study proves the proatherogenic role of monocyte-derived macrophages, as fewer monocyte-macrophages led to smaller lesions despite higher levels of proatherogenic lipoprotein particles.…”
Section: Apoe Deficiency-induced Atherosclerosissupporting
confidence: 86%
“…The apoE-deficient op mice had plasma cholesterol levels approximately 2.5-fold higher than their apoE deficient littermate controls, the increase occurring in the atherogenic VLDL ϩ LDL fractions [45]. This finding confirms the hypolipidaemic effect of M-CSF that had been observed in humans, primates, and rabbits [50][51][52].…”
Section: Apoe Deficiency-induced Atherosclerosissupporting
confidence: 76%
See 2 more Smart Citations
“…10 Macrophages, participating in both lipid metabolism and inflammation, are intimately involved in all phases of atherosclerosis, from development of the fatty streak to processes that ultimately contribute to plaque rupture and myocardial infarction. 11 Macrophage expression of certain genes is atheroprotective, whereas inadequate expression or lack of expression of these same genes in macrophages increases atherosclerosis. 12 It has been reported that macrophage LXRa is required for antiatherogenic activity of LXRa agonists.…”
Section: Introductionmentioning
confidence: 99%